Advanced abdominal pregnancy: diagnosis, evaluation and surgical management in a resource constrained setting - Elijah, Regis (Department of Obstetrics and Gynaecology, 2022)
Introduction Advanced abdominal pregnancy (AAP) is a pregnancy of over 20 weeks gestation, with a foetus living, or showing signs of having once lived and developed, in the mother's abdominal cavity. It is a rare obstetric complication associated with high maternal and perinatal morbidity and mortality. The question of whether to leave the placenta in or to remove it has been the subject of debate. When such cases present outside high resource settings, where a multi-disciplinary approach may not be possible, there are many challenges to effective treatment. The management of this rare but serious complication of pregnancy at Rob Ferreira Hospital (RFH), a rural provincial tertiary hospital, in Mpumalanga, was investigated. Methods This was a retrospective observational study of patients with AAP identified from theatre registers from January 2011 to January 2018 at RFH. Data was collected on patient demographics, diagnostic challenges, preoperative evaluation, and surgical management particularly of the placenta, and outcomes. Delivery data for RFH was retrieved from the provincial database. Results There were 26 cases of AAP identified, for which 21 folders could be retrieved from the registry. The incidence of AAP was 66.2 per 100, 000 deliveries. Abdominal pain was a presenting complaint in 100% of patients. Ultrasound scan (USS) accuracy, prior to surgery, was eventually 90.5%. However, for 61.9% the diagnosis of AAP was missed at initial USS and for 33% of these, AAP was only diagnosed after failed attempts at induction of labour (IOL). AAP was diagnosed intra-operatively in 9.5%, for a supposed caesarean delivery and 19 (94.7%) were diagnosed pre-operatively. Intra-operatively, 36.8% patients had placental site bleeding for which partial placental removal was 2 necessary in 71.4%. This group had more adverse maternal outcomes. For 73.7% of patients there was no bleeding from placental bed and the placenta was left in situ; but 7.1% required relook laparotomy for haemorrhage. There was one maternal death. Overall neonatal survival rate was 14.3% and pregnancy loss rate was 71.4%. Conclusion This study shows that planned management of AAP in a resource constrained setting with tailored approach and management, can be performed without compromising maternal outcomes. However, poor outcomes occurred when pre-operative diagnosis was not made and AAP was discovered during emergency CS, emphasising the importance of antenatal diagnosis. USS and a high index of suspicion remains the best diagnostic tool. From this study it appears safe to leave the placenta undisturbed unless it can be safely removed, or the patient is already bleeding from the placental site. There were very low neonatal survival rates, and this needs to inform counselling of patients with AAP.